Context-Clues-Based-Strategy for Better Reading Comprehension Skill - Lailiy Kurnia Ilahi; Rachmad Hidayat (Technium Social Sciences Journal, 2023)
In this study, eighth graders at an Islamic Junior High School in Pamekasan were taught reading comprehension utilizing a context-clues-based strategy. The pre-experimental design was employed, while the instrument used to collect the data was a reading test. The pre-test and post-test were two separate tests. The eighth graders (VIII-C) class served as the study’s sample. The results showed that using the context-clues-based strategy led to an improvement. To determine whether the hypothesis was accepted or rejected, the researcher conducted a t-test. The outcome revealed that the Ha is accepted, while the Ho is rejected, or t-score > t-table or 7.405 > 2.048. Students’ reading comprehension skills are considerably improved by using a context-clues-based strategy.